The Notary’s Prudential Principle as a Safeguard for the Validity of Authentic Deeds - Nurhanto Nurhanto; Ahmad Sobari (PPPM, Sekolah Tinggi Ilmu Hukum (STIH) Biak-Papua, 2026)
Authentic deeds executed by notaries occupy a pivotal position within the Indonesian legal system, as they serve as written instruments of evidence that ensure legal certainty and protection for the parties involved. Nevertheless, violations of the legal requirements governing deed preparation, as well as the failure to apply the prudential principle, may result in the degradation of a deed’s evidentiary value and, in certain circumstances, its annulment. This study aims to analyze the legal status of authentic deeds within the Indonesian legal framework and to examine their role, function, and evidentiary strength in civil proceedings. The research employs a normative juridical method using statutory, conceptual, and case-based approaches through an extensive review of legislation, legal doctrines, and scholarly literature. The findings demonstrate that authentic deeds possess perfect evidentiary force in terms of external, formal, and material proof, as recognized under the Indonesian Civil Code and the Law on Notarial Office. The application of the notary’s prudential principle constitutes a fundamental factor in preserving the validity and evidentiary integrity of authentic deeds. The study concludes that notarial professionalism and strict compliance with legal procedures are essential for ensuring legal certainty, legal protection, and substantive justice.